PENGARUH ADVERTISING DAN HARGA PENJUALAN PAKET UMRAH PLUS WISATA TERHADAP MINAT BELI (Studi Pada PT.Sanabil Madinah Barakah Bandung) - Agriya Fanny Pratama; Adi Suparwo (LPPM Universitas Adhirajasa Reswara Sanjaya, 2021)
This research aims to know and explain the influence of advertising and the price given to the purchase intention in PT. Sanabil Madinah Barakah Bandung. The methods used in this study are descriptive verificative with multiple linear regression analyses. The population obtained is all service users who have purchased Umrah package plus tour at PT. Sanabil Madinah Barakah Bandung amounted to 193 people, while the sampling techniques using probability sampling techniques with simple random sampling or random technique with a sample number of 66 respondents and the data retrieval techniques used are questionnaires. The result of this study that based on partial analysis known free variables are advertising positive effect on the purchase intention and also the price positively affect the purchase intentiont while based on simultaneous analysis advertising and prices simultaneously positively affect the purchase intention. Therefore, the company by implementing advertising strategy and the right price can increase the interest in buying. This research is different from other researchers that there is no previous researcher discussing the strategy of promotional strategies through advertising on tour and travel companies, especially in PT Sanabil Madinah Barakah Bandung, besides the indicators of the price variables have greater value and influence than advertising variables.